2021
DOI: 10.1111/1471-0528.16778
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic improvement after mesh removal: a prospective longitudinal study of women with urogynaecological mesh complications

Abstract: Objective To compare clinical characteristics and outcomes in patients undergoing excision of polypropylene urogynaecological mesh for pain, mesh exposure or both.Design Prospective, longitudinal cohort.Setting Academic tertiary referral centre.Population Women undergoing complete vaginal mesh excision for mesh exposure and/or pain.Methods Clinical and patient-reported outcomes assessing pain (visual analog scale, VAS), bother (Pelvic Floor Distress Inventory, PFDI) and functional impact (Pelvic Functional Imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…It is therefore possible that the true incidence of SUI after TETOT has not been accurately reported. High rates of loss to follow‐up (60%−70%) have been common in studies reporting outcomes after mesh excision 8,12 . A review of the literature revealed commonality between other studies—frequently, studies reporting outcomes of stress incontinence after mesh excision typically carry heterogenous groups of MUT routes, report outcomes over a short period of time, and are limited to vaginal excisions 8,9,20–23 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is therefore possible that the true incidence of SUI after TETOT has not been accurately reported. High rates of loss to follow‐up (60%−70%) have been common in studies reporting outcomes after mesh excision 8,12 . A review of the literature revealed commonality between other studies—frequently, studies reporting outcomes of stress incontinence after mesh excision typically carry heterogenous groups of MUT routes, report outcomes over a short period of time, and are limited to vaginal excisions 8,9,20–23 .…”
Section: Discussionmentioning
confidence: 99%
“…8,12 A review of the literature revealed commonality between other studies-frequently, studies reporting outcomes of stress incontinence after mesh excision typically carry heterogenous groups of MUT routes, report outcomes over a short period of time, and are limited to vaginal excisions. 8,9,[20][21][22][23] These rates cannot be generalized to those undergoing TETOT, in the longterm. Rates of worsening and new stress incontinence provide clinicians with essential information to counsel women.…”
Section: Stress Incontinencementioning
confidence: 99%
See 2 more Smart Citations
“…Once integrated into pelvic tissues, mesh cannot be easily removed (if at all) and in some instances the reoperation results in significant removal of portions of the vagina. Despite mesh removal, often complications (especially pain) fail to resolve [82]. This is particularly concerning given that approximately 12.6% of women will undergo surgery to repair POP by age 80 and this percentage is expected to rise (∼50%) by 2050 [79,83].…”
Section: Biomaterials Interventions For Pelvic Organ Prolapse (Pop)mentioning
confidence: 99%